The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s10535-011-0016-8
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a type 3 metallothionein isolated from Porteresia coarctata

Abstract: Metallothioneins are involved in detoxification of heavy metals. A cDNA encoding type 3 metallothionein (PcMT3) was isolated from the salt stressed leaf cDNA library of Porteresia coarctata (Roxb.) Tateoka (wild rice) that grows well in the heavy metal laden estuarine soils. The PcMT3 cDNA (581 bp) encodes a protein of 64 amino acids. PcMT3 is highly homologous (82 %) to OsMT-I-3a of rice, but is unique from other type 3 plant MTs due to the presence of an additional glycine residue in the C-terminal domain. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Other hormone-responsive elements found in pMT promoters include ERE (ethylene), MeJARE (methyl jasmonate), GARE (gibberellic acid), and SARE (salicylic acid). The discovery of these specific genetic instructions begins to answer the question why particular pMT genes are observed under certain conditions, and the identification of putative root-specific 28,66 and fruit-specific elements 67 further suggests that specific spatial expression is also programmed in these regions. It is clear that the identification and presence of elements responsive to various signals can provide important insights into the intricate interplay of pMT genes in planta, and, ultimately into their physiological function.…”
Section: In Vivo Studies: In Search For Physiological Functionsmentioning
confidence: 99%
“…Other hormone-responsive elements found in pMT promoters include ERE (ethylene), MeJARE (methyl jasmonate), GARE (gibberellic acid), and SARE (salicylic acid). The discovery of these specific genetic instructions begins to answer the question why particular pMT genes are observed under certain conditions, and the identification of putative root-specific 28,66 and fruit-specific elements 67 further suggests that specific spatial expression is also programmed in these regions. It is clear that the identification and presence of elements responsive to various signals can provide important insights into the intricate interplay of pMT genes in planta, and, ultimately into their physiological function.…”
Section: In Vivo Studies: In Search For Physiological Functionsmentioning
confidence: 99%
“…In a study of the promoter sequence of the Fagopyrum esculentum FeMT3 gene, Nikolić et al (2010) showed the presence of four MRE elements. Analyses of type 3 metallothionein gene promoters in Populus alba (MT3b) (Bereta et al, 2009), Elaeis guineensis (MT3-B) (Siti Nor Akumar et al, 2002) and Porteresia coarctata (PcMT3) (Usha et al, 2011) revealed the presence of MREs. Usha et al (2009) described the sequences of three Prosopis juliflora MTs that do not contain the MRE motif within the promoter region.…”
Section: Identification Of Putative Cis Elements Connected With the Pmentioning
confidence: 99%
“…However, they are also present in some sewage sludge, organic and inorganic fertilizers and fungicides and they are emitted by various human activities in amounts that could be toxic (Mantovi et al 2003, Figueiredo et al 2007. Some plant species can withstand the excess of heavy metals from the environment compartmentalizing, chelating with metallothionein or excluding them (Cheng 2003, Usha et al 2011. Cu and Zn may accumulate in plant tissues, causing many physiological and biochemical changes, growth reduction and yield loss particularly after chronic exposure (Wannaz et al 2003, Mazen 2004.…”
Section: Introductionmentioning
confidence: 99%